Toward a porcine in vivo model to analyze the pathogenesis of TLR5-dependent enteropathies. Issue 1 (9th November 2020) - Pieper, Robert; van Best, Niels; van Vorst, Kira; Ebner, Friederike; Reissmann, Monika; Hornef, Mathias W.; Fulde, Marcus
ABSTRACT: Non-communicable diseases, such as the metabolic syndrome and inflammatory bowel disease, constitute serious public health threats in developed countries. Besides environmental factors, genetic predispositions contribute to the onset and progression of the disease. State-of-the-art mouse models recently highlight the involvement of Toll-like receptor 5 (TLR5)–driven microbiota composition in the development of metabolic disorders. Here, we discuss the causes and consequences of an altered enteric microbiota and provide information on a similar mechanism in another species, the pig. We show for the first time that a single nucleotide polymorphism in the porcine TLR5 gene conferring impaired functionality is associated with changes in the intestinal microbiota in adult sows and neonatal piglets. Changes in the developing adaptive cellular immune response support the concept of TLR5-driven changes of the microbe-host interplay also in the pig. Together, these findings suggest that pigs with impaired TLR-functionality might represent a model for TLR5-driven diseases in humans.